Numerical computational fluid dynamics (CFD) simulation study based on plunger gas lift test - Li, Nan; Cao, Guangqiang; Jiang, Yixin; Gao, Haohong; Wang, Haoyu; Wu, Qiubo; Qi, Wei; Ma, Wentao (Frontiers in Earth Science, 2023)
In order to explore the feasibility of the calculated fluid dynamics (CFD) method for plunger gas lift and the flow pattern in a long wellbore, a lab simulation test was conducted to verify the reliability of the CFD simulation results. Verification data were provided for CFD simulation through carrying out a plunger gas lift lab test for vertical wells, identifying the plunger movement patterns and delivery rates under different flow pressures, and determining the minimum plunger startup pressure or differential pressure and leakage, and an identical CFD physical model was created on the basis of the lab test model, CFD dynamic grid programming and CFD simulation were conducted under test conditions, and a comparison of the simulation and test results was made to identify the calculation accuracy and the rationality of the CFD model and method; finally, boundary conditions such as temperature and pressure were set according to the actual long wellbore (200m) conditions, the CFD simulation was performed, and the impacts of the downhole conditions on the gas lift performance were analyzed, so as to develop CFD calculation methods to predict the bottom-hole flow pressure, plunger speed, and delivery rate. The results show: the average plunger speed range is 7.74-22.5m/s when the flow pressure varies from 199.77kPa to 632.93kPa, and the leakage rate increases in a nearly linear way with the speed; compared with the lab test results, the simulation results from the created dynamic grid model and multi-phase turbulent flow model have the leakage error of 7.2% and the plunger speed average error is smaller than 11.1%; under long-wellbore conditions, the plunger lift speed shows the change pattern of increasing and then decreasing, the wellbore pressure has a wave-like drop, and in addition to this pressure drop characteristic, the fact that the plunger startup pressure differential increases with the wellhead pressure should be considered (when the bottom-hole pressure is 15MPa, the wellhead pressure must not exceed 10MPa).